Analisis Pengukuran Produk HKZL PT.Gradien Manufaktur Indonesia Menggunakan Multivariat Gage, Repeatability and Reproducibility (GRR) Melalui Analisis Faktor - Selvi Marcelina; Asep Solih Awalluddin; Arief Fathcul Huda; Rismawati Ramdani; Esih Sukaesih (KUBIK, 2021)
Measurement data is often used in determining the quality of a product. Some of the results in measurement present multivariate properties, meaning that there are many characteristics of quality. Many variables are measured to be used as a reference in improving product quality on the company's predetermined standards. But in reality, there are variations in the size or size of products that do not meet the standard of measurement used by the company. In this case, the correlation structure between quality characteristics is often overlooked. Variables that correlate in a group, but with relatively small correlations between other groups are more suitable tasks for factor analysis. Therefore, to solve The purpose of multivariate GRR through factor analysis is to identify the covariance structure between several quality characteristics in improving product quality using multivariate Gage, Repeatability and Reproducibility (GRR) through factor analysis, and find out if the HKZL product measurement system is in PT. Indonesia's Manufacturing Gradient is accepted or does not use the multivariate Gage, Repeatability and Reproducibility (GRR) method through factor analysis. In practice, the analysis step has been prepared and applied to the measurement of HKZL products in PT. Indonesian Manufacturing Gradient. The results were obtained from the measurement system on HKZL products in PT. The Indonesian Manufacturing Gradient is not accepted, meaning that the resulting product is HKZL has quality beyond the company's standards (quality standards), so it can be concluded that the HKZL product making machine is in poor condition to use.